Hybrid optimization model for conjunctive use of surface and groundwater resources in water deficit irrigation system - Karthikeyan Moothampalayam Sampathkumar (IWA Publishing, 2021)
The increasing demand for food production with limited available water resources poses a threat to agricultural activities. Conventional optimization algorithms increase the processing stage and perform in the space allocated from user. Therefore, the proposed work was used to design better performance results. The conjunctive allocation of water resources maximizes the net benefit of farmers. In this study, the novel hybrid optimization model developed is the first of its kind and was designed to resolve the sharing of water resource conflict among different reaches based on a genetic algorithm (GA), bacterial foraging optimization (BFO) and ant colony optimization (ACO) to maximize the net benefit of the water deficit in Sathanur reservoir command. The GA-based optimization model considered crop-related physical and economic parameters to derive optimal cropping patterns for three different conjunctive use policies and further allocation of surface and groundwater for different crops are enhanced with the BFO. The allocation of surface and groundwater for the head, middle and tail reaches obtained from the BFO is considered as an input to the ACO as a guiding mechanism to attain an optimal cropping pattern. Comparing the average productivity values, policy 3 (3.665 Rs/m3) has better values relating to policy 1 (3.662 Rs/m3) and policy 2 (3.440 Rs/m3). Thus, the developed novel hybrid optimization model (GA-BFO-ACO) is very promising for enhancing farmer's net income and can be replicated in other irrigated regions to overcome chronic water problems. The productivity value of policy 3 was 6.54% greater than that of policy 2, whereas that of policy 1 was 6.45% greater. Overall, the comparison shows that the better performance analysis of various optimization was done successfully. HIGHLIGHTS Hybrid optimization model using three meta-heuristic algorithms (GA, BFO and ACO) was developed.; The developed hybrid model is used for optimizing the cropping area, conjunctive water allocation and net returns for different reaches.; The net returns from the developed hybrid model (GA-BFO-ACO) outperform GA- BFO model.; The developed hybrid model is the first of its kind to unravel the sharing of water resources for profit maximization which can be adopted globally to overcome chronic water problems.;